EFFECT OF ANNEALING ON THE MECHANICAL PROPERTIES OF FUSED DEPOSITION MODELING 3D PRINTED PLA - Natayu, Amartya; Muhammad, Azka Aulia; Tumada, Azhari; Saptaji, Kushendarsyah; Trisnadewi, Titin; Triawan, Farid; Ramadhan, Anwar Ilmar; Azhari, Azmir (Jurnal Rekayasa Mesin, 2024)
Additive manufacturing or 3D printing is a rapidly moving fabrication technology with many usages in various fields. One of the methods used in 3D printing is Fused Deposition Modeling (FDM), where polylactic acid (PLA) filament is melted and deposited layer by layer to form the desired parts. This study explored the impact of annealing on the mechanical properties of 3D printed PLA specimens. Tensile specimens were produced using FDM following ASTM D638 standards. The specimens were annealed at 95°C and 145°C for 30, 60, and 120 minutes. Two untreated specimens served as benchmarks. Tensile tests were conducted on all specimens to evaluate their mechanical properties. The most optimal result was achieved with annealing at 95°C for 30 minutes, producing Young’s modulus of 3.3 GPA and the highest ultimate tensile strength (UTS) of 38.9 MPa. Other parameters resulted in lower properties compared to the untreated specimens.